“She was finally mine”: the moral experience of families in the context of trisomy 13 and 18– a scoping review with thematic analysis - Zoe Ritchie; Gail Teachman; Randi Zlotnik Shaul; Maxwell J. Smith (BMC Medical Ethics, 2024)
Abstract Introduction The value of a short life characterized by disability has been hotly debated in the literature on fetal and neonatal outcomes. Methods We conducted a scoping review to summarize the available empirical literature on the experiences of families in the context of trisomy 13 and 18 (T13/18) with subsequent thematic analysis of the 17 included articles. Findings Themes constructed include (1) Pride as Resistance, (2) Negotiating Normalcy and (3) The Significance of Time. Interpretation Our thematic analysis was guided by the moral experience framework conceived by Hunt and Carnevale (2011) in association with the VOICE (Views On Interdisciplinary Childhood Ethics) collaborative research group. Relevance This article will be of interest and value to healthcare professionals and bioethicists who support families navigating the medically and ethically complex landscape of T13/18.